A cross-hospital cost and quality assessment system by extracting frequent physician order set from a nationwide Health Insurance Research Database. Issue 3 (July 2015) - Chen, Kuo-Hsin; Wu, Jin-Ming; Ho, Te-Wei; Yu, Hwan-Jeu; Lai, Feipei
Highlights A system that provides a convenient way for physicians to retrieve and compare clinical pathways among health care providers about herniorrhaphy. The frequent physician order sets were derived from the National Health Database. A higher consistency index leads to lower recurrence rates.